1989
DOI: 10.1177/002221948902200812
|View full text |Cite
|
Sign up to set email alerts
|

The Locus of So-Called IQ Test Results in Reading Disabilities

Abstract: It would appear the question of relevance of IQ in the assessment and remediation of children with RD is not quite the relevant question to ask, if only traditional intelligence tests are the focus. From the psychoeducational point of view of refining diagnosis, and from the administrative perspective of accountability, it would be helpful to accept a threshold of something like an IQ of 85 as the lower bound in defining learning or reading disabilities. A discrepancy from this threshold as derived from regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several researchers have suggested that IQ has limited value for the differential diagnosis of reading disability (e.g., Siegel, 1988). However, it is argued here that IQ tests should not be rejected completely; in the present study, it is included as a threshold concept where an IQ of 85 is conceptualized as the lower bound in defining reading disabilities (Leong, 1989).…”
Section: Methods Samplementioning
confidence: 86%
“…Several researchers have suggested that IQ has limited value for the differential diagnosis of reading disability (e.g., Siegel, 1988). However, it is argued here that IQ tests should not be rejected completely; in the present study, it is included as a threshold concept where an IQ of 85 is conceptualized as the lower bound in defining reading disabilities (Leong, 1989).…”
Section: Methods Samplementioning
confidence: 86%
“…There is no consensus for the average intelligence below which reading dis ability cannot be attributed to a specific de velopmental dyslexia syndrome. While some set a minimum score of 90 points, others con sider 85 points as the cutoff IQ level [9].…”
Section: Minor Neurological Signsmentioning
confidence: 99%
“…Such discussions would not be necessary if we placed the concept of intelligence in proper perspective. Leong (1989), for example, suggested that IQ be treated as a threshold concept. An IQ of 85 is conceptualized as the lower bound in defining learning disabilities.…”
Section: Intelligence Should Not Take Center Stagementioning
confidence: 99%